Static vs. dynamic impacts of unbundling: Electricity markets in South America - Dominik Schober (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Ownership unbundling and third party access are discussed as two options of unbundling in both the literature and political discussions. Focusing on the South American electricity sector, I contrast static and dynamic impacts of ownership unbundling and third party access regimes on customer prices. Substantially different results are found using dynamic rather than static analysis. In particular, negative short term effects of ownership unbundling found in static models are approximately cancelled out by subsequent positive impacts in the dynamic model. Third party access seems to allow for similar benefits while avoiding the (restructuring) costs of ownership unbundling. Previously estimated static models thus appear to suffer from either omitted variable biases or endogeneity problems of static non-difference models.
urn:nbn:de:bsz:180-madoc-337961
Keywords: L42; L51; L52; L94; 330; (De)Regulation; dynamic panel data analysis; electricity markets; market organization; unbundling; non-discriminatory (third party) access